Evolutionary game analysis for third-party governance of environmental pollution - Xu, Ran; Wang, Yanrong; Wang, Wenbin; Ding, Yongxin (Journal of ambient intelligence and humanized computing, 2019)
Environmental pollution in China presents complex features include regional, agglomeration, periodicity, diversity and multiple. The government-led environmental pollution control mode has been unable to adapt to the current grim situation, so the inevitable trend of the development of Chinese environmental pollution governance system is the third-party governance with diversified participation. The tripartite evolutionary game model is built, including the governments, environmental services companies and pollutant discharging enterprise, and the key factors affecting the dynamic evolution of game equilibrium are explored. Then, the effects of third-party governance punishment strategy of environmental pollution under multiple scenarios and the stable equilibrium points are also discussed. Results are show as follow: (1) the “public-private-partnership” mode is the key point to increase the environmental public interest in the process of achieving economic benefits; (2) The government can not only take punishment as the main regulatory measures, but also need to establish a contractual “public and private” governance system. At the same time, government should establish governance authority and fulfill the roles and responsibilities of the coordinator, guider and supervisor; (3) the implementation of government supervision must be combined with Chinese economic and society development and environmental pollution, and guided by marketization, legalization, specialization, and industrialization. According to the degree of perfection of the system of third-party governance of environmental pollution, the penalties for illegal actions are dynamically adjusted in time. It is necessary to push the choice of “private subject” to public rationality, so as to guide environmental pollution control to Chinese good governance.